Persepsi konsumen dan faktor-faktor yang mempengaruhi keputusan pembelian beras premium - Mahendra, Mas'ud; Mamilianti, Wenny (University of Islam Malang, 2020)
Increasing rice consumption in Indonesia provides a great opportunity in the rice business. Rice's business development is marked by the emergence of rice producers with various brands and qualities. Improving the standard of living of the Indonesian people also affects consumer behavior in choosing rice to be consumed. This change in consumer behavior is responded by rice producers by producing super quality rice or often called premium rice. The rise of premium rice sales now needs a study of consumer behavior towards premium rice purchasing decisions. This study aims to analyze consumers' perceptions of premium rice and analyze the factors that influence consumer behavior in purchasing premium rice. The study's location was determined intentionally in the city of Pasuruan, and respondents were 100 rice consumers through convenience sampling. The method of data analysis uses tabulation description analysis and regression Logit models. The results showed consumers' perceptions of premium rice by 47% the price of premium rice is higher, 53% the color is perfect, 56% expressed better dexterity, 51% better aroma, 47% endurance as well as other rice, 78% uniformity of grain better, and 49% stated that cleanliness was the same as other rice. Consumer perception of the belief in premium rice that 47% of consumers stated that premium rice is better than medium rice. The factors that significantly influence the purchase of premium rice are education, income, and the number of household members.